PENERAPAN MODEL READING GUIDE DALAM MENINGKATKAN PEMAHAMAN MEMBACA SISWA KELAS V PADA PEMBELAJARAN IPS MIN 2 ACEH BARAT - Asfi, Asfi Mujiati; Maya Agustina; Abidah (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2025)
The application of the reading guide learning model in the teaching and learning process in social studies learning is one effort to improve student learning outcomes. This research aims to improve the reading ability of class V MIN 2 West Aceh students, to determine the increase in student learning outcomes by implementing the reading guide model in the reading comprehension of class V MIN 2 West Aceh students. This research is Classroom Action Research (PTK). The subjects in this research were 33 students of class V MIN 2 West Aceh. The data collection techniques used are through observation, tests and documentation. The data analysis technique was carried out using qualitative descriptive. Based on the research results, it shows that classical student learning outcomes in the pre-cycle were 12.12%, in the first cycle it increased to 57.57% and in the second cycle it increased further to 90.90%. Based on the results of observations of student activity in cycle I, it reached the sufficient category with a score of 76.92% and in cycle II it increased with a score of 94.23% in the very good category. So it can be concluded that the reading guide learning model can improve the reading comprehension abilities of class V MIN 2 West Aceh students in social studies learning.